Coherent twin-oriented Al3Sc-based precipitates in Al matrix. (May 2023) - Shanmugam, Sankaran; Peterlechner, Martin; Iskandar, Mohamad Riza; Saikia, Ujjal; Kulitckii, Vladislav; Lipińska-Chwałek, Marta; Mayer, Joachim; Rösner, Harald; Hickel, Tilmann; Divinski, Sergiy V.; Wilde, Gerhard
Abstract: Al3 (Sc, Zr, Ti) nanoparticles with an ideal twin-type orientation relationship to Al host matrix were found in cold-rolled and subsequently annealed Al-based alloy. Atomic-scale investigations using high-resolution scanning transmission electron microscopy identified particles that form prominent coherent (111) twin-type interfaces along their longer facets and semi-coherent twin interfaces on their shorter facets. Ab-initio calculations showed that a coherent Al/Al3 Sc twin-like phase boundary corresponds to a local energy minimum. A model is proposed explaining the formation of the twin orientation relationship of an Al3 Sc nanoparticle with the Al host matrix. Graphical abstract: